(untitled) (Global Journal of Medical Research, 2020)
Introduction: Atherosclerosisis highly linked to heart attacks and strokes which are two leading cause of death in the United States according to the Center of Disease Control and Prevention (CDC).The increasing severity of atherosclerosis comes from the instance that symptoms usually appear at late stages of the disease. In addition, the mechanisms by which atherosclerosis forms, develops, and triggers the onset of myocardial infarction is not fully understood. In this study, we simulated the effect that atheromas have on the blood flow physics and the correlation that these flow disturbances may have on the onset of myocardial infarction. Materials and Methods: A 3D virtual geometry of an idealized coronary artery with a hemispherical obstruction was created using human anatomical dimensions. All Ansys simulations performed in this study used laminar flow conditions with density = 1060 kg/m3, viscosity = 3.5 centipoise. We applied a physiological velocity waveform at the inlet and a zero relative-pressure condition at the outlet. No slip boundary conditions were prescribed to the coronary artery walls.